Influence of animal husbandry practices on void spot assay outcomes in C57BL/6J male mice. Issue 2 (12th November 2014) - Keil, Kimberly P.; Abler, Lisa L.; Altmann, Helene M.; Bushman, Wade; Marker, Paul C.; Li, Lingjun; Ricke, William A.; Bjorling, Dale E.; Vezina, Chad M.
Abstract : Aims: Mice are increasingly being used as models to investigate aspects of urinary dysfunction that humans with lower urinary tract symptoms (LUTS) experience. One method used to examine voiding function is the spontaneous void spot assay. The purpose of this study was to characterize and identify animal husbandry conditions that might confound results of the spontaneous void spot assay in male C57Bl/6J mice. Methods: Mice were placed in cages lined with filter paper for 4 hr and urine was visualized with UV transillumination. Voiding parameters including urine spot number, spot size, total urine area, primary void area, corner and center voiding were quantified. Results: Adult male mice void more frequently with advancing age and a subpopulation (5–10%) display a frequent spotting pattern at 6–9 weeks of age. Voiding was not significantly different in male mice weaned to group housing (4–6 per cage) versus single housing, and was not altered when they were used as breeders. Voiding was changed upon transferring group housed adult males to single density cages, which decreased total urine area. Repeated assays of male voiding behavior over three consecutive days increased primary void area by the third day of monitoring and revealed that voiding behavior is impacted by routine cage changes and time of day. Conclusions: Together these results identify housing and husbandry practices that influence male voiding behaviors in the spontaneous void spot assay and will inform voiding behavior analyses conducted with male C57Bl/6J mice. Neurourol. Urodynam. 35:192–198, 2016 . © 2014 Wiley Periodicals, Inc.